Integrated Membrane-Electrode-Assembly Photoelectrochemical Cell under Various Feed Conditions for Solar Water Splitting. Issue 5 (10th December 2018) - Kistler, Tobias A.; Larson, David; Walczak, Karl; Agbo, Peter; Sharp, Ian D.; Weber, Adam Z.; Danilovic, Nemanja
Abstract : Photoelectrochemical (PEC) water splitting has the potential to significantly reduce the costs associated with electrochemical hydrogen production through the direct utilization of solar energy. Many PEC cells utilize liquid electrolytes that are detrimental to the durability of the photovoltaic (PV) or photoactive materials at the heart of the device. The membrane-electrode-assembly (MEA) style, PEC cell presented herein is a deviation from that paradigm as a solid electrolyte is used, which allows the use of a water vapor feed. The result of this is a correspondent reduction in the amount of liquid and electrolyte contact with the PV, thereby opening the possibility of longer PEC device lifetimes. In this study, we demonstrate the operation of a liquid and vapor-fed PEC device utilizing a commercial III-V photovoltaic that achieves a solar-to-hydrogen (STH) efficiency of 7.5% (12% as a PV-electrolyzer). While device longevity using liquid water was limited to less than 24 hours, replacement of reactant with water vapor permitted 100 hours of continuous operation under steady-state conditions and diurnal cycling. Key findings include the observations that the exposure of bulk water or water vapor to the PV must be minimized, and that operating in mass-transport limited regime gave preferable performance.